SUPPLY CHAIN RISK MANAGEMENT (SCRM) ANALYSIS ON THE SUPPLY CHAIN OF HALAL FOOD PRODUCTS USING SCOR, HORR AND PARETO DIAGRAM METHOD (CASE STUDY ON IBU MIMIN’S CHICKEN SLAUGHTER HOUSE) - Nova Septi Sanjaya; Kuncorosidi Kuncorosidi (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2021)
Chicken Slaughterhouse is a chicken slaughterhouse that has a big opportunity to be developed as a business in the future. The people's need for chicken meat continues to increase. Chicken meat as a provider of protein, energy, vitamins and minerals is increasing along with the increasing public awareness of nutritional needs in order to improve the quality of life. Halal Supply Chain Risk Management is one of the most important factors for Muslim consumers, from Chicken Slaughterhouses to markets and food vendors with processed chicken who buy supplies from Ibu Mimin’s Chicken Slaughter House to consumers, both consumers from RPA Ibu Mimin and restaurant consumers. In this study, all activities at Ibu Mimin's Chicken Slaughter House were identified starting from mapping activities, determining risk events, risk agents, calculating Aggregate Risk Potential and risk mitigation measures in the Slaughterhouse supply chain by adopting the SCOR model, namely plan, source, make, deliver, and return and HOR (House of Risk). The results showed that there were 30 risk events and 11 risk sources.